Simultaneous Estimation of Cefoperazone and Sulbactam in Bulk and Multicomponent Formulation - THOMAS, ASHA; KANDGAONKAR, S.A.; KOTHAPALLI, LATA; JANGAM, SUMITRA; BODKHE, S.; PATANKAR, MANISHA (Asian Journal of Chemistry, 2010)
A novel, simple, sensitive, rapid, accurate and economical spectrophotometric method has been developed for the simultaneous estimation of cefoperazone sodium and sulbactam sodium in bulk and combined dosage form. This method involves solving of simultaneous equations based on measurement of AUC at two wavelengths ranges 259-269 and 220-228 nm. Both the drugs obeyed the Beer's law in the concentration ranges employed for this method. The results of the analysis were validated statistically and by recovery studies.